2020
DOI: 10.3390/su12062341
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Sharing Platforms: An Empirical Study of the Factors Affecting Continued Use Intention

Abstract: Under the background of the constant development of sharing economy and constant upgrade of Internet technologies, various knowledge sharing platforms have emerged in recent years. As a new form for sharing economy, knowledge sharing platforms have made great strides, thus, providing new channels of knowledge acquisition, knowledge sharing and individual knowledge storage for users. Nevertheless, knowledge sharing platforms are still faced with problems, such as uneven product quality (Content quality) and poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 73 publications
7
48
3
2
Order By: Relevance
“…Attitudes, subjective norms, and positive and negative expectations have significant impacts on consumers’ willingness to buy sporting goods online, and past behavior and frequency of desire affect consumers’ intentions [ 38 ]. Pang et al showed that perceived usefulness and satisfaction have important impacts on the continuous intention to use knowledge sharing platforms, which should strengthen their content quality control to ensure consistency between service quality and payment, so as to improve platform quality [ 39 ]. Customer participation in brand building activities has direct and indirect impacts on satisfaction and loyalty, which are partly influenced by brand experience.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Attitudes, subjective norms, and positive and negative expectations have significant impacts on consumers’ willingness to buy sporting goods online, and past behavior and frequency of desire affect consumers’ intentions [ 38 ]. Pang et al showed that perceived usefulness and satisfaction have important impacts on the continuous intention to use knowledge sharing platforms, which should strengthen their content quality control to ensure consistency between service quality and payment, so as to improve platform quality [ 39 ]. Customer participation in brand building activities has direct and indirect impacts on satisfaction and loyalty, which are partly influenced by brand experience.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Perceived usefulness referred to user-perceived real performance from information system after using it. Perceived usefulness towards user satisfaction had been analyzed previously by Pang et al (2020) and Rana and Dwivedi (2015), who found proof that the positive effect of perceived usefulness towards user satisfaction, while research result by Kim and Qu (2014) found that did not affect. Next, Intention to use gave positive and significant effect statistically towards e-local tax return usage (H10).…”
Section: Discussionmentioning
confidence: 88%
“…Although, research by Bhattarai and Maharjan (2020) stated that perceived usefulness did not affect the intention to use. User satisfaction can be increased if the system is useful (Pang et al, 2020;Rana & Dwivedi, 2015). If taxpayers believe that the system has usefulness, such as can increase productivity and performance, then it can increase the intention to use and user satisfaction towards e-local tax return.…”
Section: Perceived Usefulnessmentioning
confidence: 99%
“…One of the most important functions of the platform is to provide information sharing [22]. Information is the representation of knowledge in the forms of explicit or implicit.…”
Section: Introductionmentioning
confidence: 99%